Faces of Joblessness in Estonia A People-centred perspective on employment barriers and policies - Browne, James (OECD Publishing, 2018)
In the aftermath of the financial and economic crisis, large shares of working-age individuals in Estonia either did not work or only to a limited extent. By 2013, several years after the start of the labour-market recovery, 18% were still without employment during the entire year, and a further 13% had weak labour-market attachment, working only a fraction of the year, or on restricted working hours. This paper applies a novel method for measuring and visualising employment barriers of individuals with no or weak labour-market attachment, using household micro-data. It first develops indicators to quantify employment obstacles under three broad headings: (i) work-related capabilities, (ii) incentives, and (iii) employment opportunities. It then uses these indicators in conjunction with a statistical clustering approach to identify unobserved ("latent") groups of individuals facing similar combinations of barriers. The resulting typology of labour-market difficulties provides insights on the most pressing policy priorities in supporting different groups into employment. A detailed policy discussion illustrates how the empirical results can inform people-centred assessments of existing labour-market integration measures and of key challenges across different policy areas and institutions. The most common employment obstacles in Estonia were low skill levels, health limitations and limited work experience. Financial disincentives, care responsibilities and scarce job opportunities were less widespread overall, although important barriers for some groups. A notable finding is that almost one third of jobless or low-intensity workers face three or more simultaneous barriers, highlighting the limits of narrow policy approaches that focus on subsets of these employment obstacles in isolation
Keywords: Employment; Social Issues/Migration/Health; Estonia